2019
DOI: 10.2196/13575
|View full text |Cite
|
Sign up to set email alerts
|

Exergaming Improves Executive Functions in Patients With Metabolic Syndrome: Randomized Controlled Trial

Abstract: Background Recent studies indicate that participation in exercise-related games can improve executive function, attention processing, and visuospatial skills. Objective The aim of this study was to investigate whether exercise via exergaming (EXG) can improve executive function in patients with metabolic syndrome (MetS). Methods A total of 22 MetS patients were recruited and randomly assigned to an EXG group… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
1
11
0
1
Order By: Relevance
“…Metabolic syndrome (MetS) is a serious risk factor for heart disease, stroke, and type 2 diabetes. There are numerous indicators of MetS, including hypertriglyceridemia, high blood sugar, and abdominal obesity; the incidence rate of MetS is steadily increasing [ 2 ]. Concurrently, MetS significantly lowers individuals’ quality of life (QOL) [ 3 - 6 ], which is defined as one’s level of acceptance in relation to the ideals, interests, expectations, and norms of one’s culture and value system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome (MetS) is a serious risk factor for heart disease, stroke, and type 2 diabetes. There are numerous indicators of MetS, including hypertriglyceridemia, high blood sugar, and abdominal obesity; the incidence rate of MetS is steadily increasing [ 2 ]. Concurrently, MetS significantly lowers individuals’ quality of life (QOL) [ 3 - 6 ], which is defined as one’s level of acceptance in relation to the ideals, interests, expectations, and norms of one’s culture and value system [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that exercise during the presentation of green stimuli is associated with improved attentional capture. The relationship between exercise and N2 amplitude has not been fully elucidated [38,[44][45][46]. In our previous study, the combination of visual stimulation and exercise better regulates the activity of the anterior cingulate cortex (ACC) in the prefrontal cortex than exercise alone, suggesting enhanced selective attention [44].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between exercise and N2 amplitude has not been fully elucidated [38,[44][45][46]. In our previous study, the combination of visual stimulation and exercise better regulates the activity of the anterior cingulate cortex (ACC) in the prefrontal cortex than exercise alone, suggesting enhanced selective attention [44]. N2 is strongly implicated in the ACC activity, which is part of the brain network of the prefrontal cortex, and has been suggested as an important indicator of the self-regulation of cognition and emotion [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its beneficial effects on cognitive function, the interactive characteristics of exercise with technology-based intervention promote motivation, entertainment, and excitement among the players, resulting in higher exercise adherence than regular exercise [ 79 , 94 ]. Inzitari et al [ 32 ] reported that physical exercise applied through technology-based intervention was appealing to postmenopausal women, which may help improve adherence to exercise.…”
Section: Technology-based Interventions For Health and Cognitive Bene...mentioning
confidence: 99%